2018
DOI: 10.37358/rc.18.9.6553
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Cardiac Resynchronization Therapy in Patients with Heart Failure

Abstract: Heart failure is a disease characterized by cardiac remodeling or progressive dilation of left ventricle and a consequent reduction in contraction. Ventricular remodeling has been shown to be a negative prognostic factor alone, and therefore the most beneficial drugs are those that prevent or reduce left ventricular dilation. The pharmacological therapy of heart failure, although maximal, has proven to be not fully effective. The aim of our research was to evaluate resynchronization therapy in a lot of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…The results were comparable to those obtained in similar studies that concluded that almost 50% of invasive mammary carcinomas have both receptors positive whilst 25% are lacking in them [8][9][10][11][12]. The ER+/PR-phenotype represents a distinct group because it usually is accompanied by high clinical and biological aggressiveness and have the least satisfactory response to hormone therapy in comparison to other phenotypes [13][14][15][16].…”
Section: Resultssupporting
confidence: 83%
“…The results were comparable to those obtained in similar studies that concluded that almost 50% of invasive mammary carcinomas have both receptors positive whilst 25% are lacking in them [8][9][10][11][12]. The ER+/PR-phenotype represents a distinct group because it usually is accompanied by high clinical and biological aggressiveness and have the least satisfactory response to hormone therapy in comparison to other phenotypes [13][14][15][16].…”
Section: Resultssupporting
confidence: 83%
“…Riquelme et al demonstrates in his study published in 2001 the advantages of using pure ethanol over chymopapain, which was the main nucleolytic agent used in the past. The main benefits include no local septic complications, no aseptic inflammatory complications , no allergic reactions, no major pain after treatment, no chemical discitis or intersomatic disc narrowing and a shorter recovery period for patients [6][7].…”
Section: Resultsmentioning
confidence: 99%
“…But the pediatrician with expertise in diabetes, the diabetes nursing educator, the dietitian, and the mental health expert needs to be involved in managing this disease as well. All these professions should contribute to the proper education of both the children and adolescents with type 1 diabetes and also their caregivers [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%